SOCIAL BEHAVIOUR DI PESANTREN SALAF - Arif, Mohammad (P3M IAIN KEDIRI, 2017)
Salaf pesantren is an institution that is still strongly bound by old traditions. By inheriting and maintaincontinuity of Islamic tradition developed by scholars from time to time indefinite periodesasinya, has elementswhich include clerics, students, cottage / hostel, mosque, recitals of classical texts / yellow book, applyingthe method bandongan, sorogan, wetonan, principled firmly on Islamic education material. Pesantren Salafurgently need progress in science and technology. Pesantren Salaf there are many who âfailedâ to preserve itsown leadership weights, weak in preparing a âsuccessionâ Kyai guardians comparable with the foregoing, letalone exceeded. Answering the needs of the era, schools Salaf open formal educational institutions. Sensitivitypesantren Salaf against the phenomena that appear in the society is a social concern and reflexive owned evenare characteristic. So that the aspirations of the people making the boarding school received the developmentand advancement of science and technology. The real step taken is establishing formal educational institutionsfrom kindergarten through college. The character of a scholar is asceticism and totality. On the other hand,people still expect the efficacy of the function and role of pesantren Salaf like period once, without knowing thatit is actually what is expected it is experiencing overcast condition and shrinkage. Expenses are given the addedweight and more and more, but the ability to lift a boarding school in general was declining. Source overcastcondition and depreciation mainly boils down to the weight and quality of the âclerics who brought upâ. Both interms of science, wisdom, exemplary, sincerity, and shelter to the people.Keywords : Social behavior, pesantren Salaf